Morphologic Features of ALK-negative Anaplastic Large Cell Lymphomas With DUSP22 Rearrangements. (January 2016) - King, Rebecca L.; Dao, Linda N.; McPhail, Ellen D.; Jaffe, Elaine S.; Said, Jonathan; Swerdlow, Steven H.; Sattler, Christopher A.; Ketterling, Rhett P.; Sidhu, Jagmohan S.; Hsi, Eric D.; Karikehalli, Shridevi; Jiang, Liuyan; et al.
Abstract : Systemic anaplastic large cell lymphomas (ALCLs) are classified into ALK-positive and ALK-negative types. We recently reported that ALK-negative ALCLs are genetically heterogenous. The largest subset, representing 30% of cases, had rearrangements of the DUSP22 locus. These cases had favorable outcomes similar to ALK-positive ALCL, and superior to other ALK-negative ALCLs. Here, we examined the morphologic features of these cases in more detail. First, we conducted blinded review of hematoxylin and eosin slides of 108 ALCLs from our previous study, scoring cases for the presence of 3 histologic patterns and 5 cell types. Cases then were unblinded and re-reviewed to understand these features further. DUSP22- rearranged ALCLs were more likely than other ALK-negative ALCLs to have so-called doughnut cells (23% vs. 5%; P =0.039), less likely to have pleomorphic cells (23% vs. 49%; P =0.042), and nearly always (95%) had areas with sheet-like growth (common pattern). To examine the reproducibility of these findings, we conducted blinded review of hematoxylin and eosin slides of 46 additional ALK-negative ALCLs using a 0 to 3 scoring system to predict likelihood of DUSP22 rearrangement, the results of which correlated strongly with subsequent findings by fluorescence in situ hybridization ( P <0.0001). Although all ALCLs share certain morphologic features, ALCLs with DUSP22 rearrangements show significant differences from other ALK-negative ALCLs, typically showing sheets of hallmark cells with doughnut cells and few large pleomorphic cells. These morphologic findings and our previous outcome data suggest that ALK-positive ALCLs and DUSP22- rearranged ALCLs represent prototypical ALCLs, whereas ALCLs lacking rearrangements of both DUSP22 and ALK require further study. Abstract : Supplemental Digital Content is available in the text.